Synthesis of a Cytotoxic Amanitin for Biorthogonal Conjugation. Issue 10 (3rd June 2015) - Zhao, Liang; May, Jonathan P.; Blanc, Antoine; Dietrich, David J.; Loonchanta, Anastak; Matinkhoo, Kaveh; Pryyma, Alla; Perrin, David M.
Abstract Alpha‐amanitin is an exceedingly toxic, naturally occurring, bicyclic octapeptide that inhibits RNA polymerase and results in cellular and organismal death. Here we report the straightforward synthesis of an amanitin analogue that exhibited near‐native toxicity. A pendant alkyne was readily installed to enable copper‐catalyzed alkyne–azide cycloaddition (CuAAC) to azido‐rhodamine and two azide‐bearing versions of the RGD peptide. The fluorescent toxin analogue entered cells and provoked morphological changes consistent with cell death. The latter two conjugates are as toxic as the parent alkyne precursor, which demonstrates that conjugation does not diminish toxicity. In addition, we showed that toxicity depends on a single diastereomer of the unnatural amino acid, dihydroxyisoleucine (DHIle), at position 3. The convenient synthesis of a heptapeptide precursor now provides access to bioactive amanitin analogues that may be readily conjugated to biomolecules of interest.